〈Original Papers〉マガキの新規炭酸脱水酵素 - Okumura, Nao; オクムラ, ナオ; Miyamoto, Hiroshi; ミヤモト, ヒロシ (近畿大学先端技術総合研究所, 2013)
[Abstract] In metazoans, carbonic anhydrase（CA）is a common enzyme that catalyzes the reversible hydration of carbon dioxide. CA plays important roles in many biological processes, and in molluscs several CA-like proteins are thought to be responsible for calcification in shell formation. As part of our investigation of the process of shell formation, we searched for a CA gene in the oyster Crassostrea gigas, with resultant identification of a single cDNA that encodes two CA domains. This atypical CA is similar to an α-CA and is mainly expressed in the egg. This suggests that the newly identified CA is responsible for production of bicarbonate in the early development phase prior to metamorphosis. [要旨] 炭酸脱水酵素は後生動物に広く存在しており、二酸化炭素の水和を可逆的に触媒する。機能的には様々な生命過程で重要な役割を担っており、軟体動物では炭酸脱水酵素や類似タンパク質が貝殻形成における石灰化に関与していることが示唆されている。本論文では、貝殻形成の過程を調べる研究の中で同定したマガキの新規炭酸脱水酵素について報告する。単離したcDNA は、二つのCA ドメインを有しており、典型的な炭酸脱水酵素とは構造が異なっていたが、それぞれのCA ドメインはα タイプの炭酸脱水酵素との類似性を示した。また、今回同定した新規炭酸脱水酵素は卵での発現が著しく高く、変態前の重炭酸イオンの生成を担っていると推察される。 application/pdf departmental bulletin paper